Assessment of cross-section library impact on neutron beam quality in AB-BNCT monte carlo studies - Hong-Bing Song; Jing-Gang Xu; Xiong Yang; Zhi-Feng Li; Sheng Wang; Chang-Li Ruan; Xiang-Pan Li (Scientific Reports)
Abstract This study investigated the impact of nuclear reaction cross-sections data from various nuclear data libraries on neutron parameters in Monte Carlo simulations using the PHITS code for accelerator-based BNCT (AB-BNCT). Specifically, it evaluated the effect of different proton data libraries-ENDF/B VII.1, ENDF/B VIII.1, CP2020, and JENDL-5.0-on the neutron yields from the 7Li(p, n)7Be reaction in a natural lithium target. The results showed that the calculated target neutron yields differed by up to 16.86%, with notable variations in the target neutron energy spectra. Furthermore, the study assessed the impact of neutron libraries-ENDF/B VII.1, ENDF/B VIII.0, ENDF/B VIII.1, JEFF-3.3, CENDL-3.2, and JENDL-5.0-on neutron beam parameters at the BSA exit, based on the neutron spectrum at the lithium target. It was found that the epithermal neutron intensity and fast neutron component calculated with the ENDF/B VIII.1 neutron library were 5.51%-8.61% and 19.04%-63.94% higher, respectively, than that obtained with the other neutron libraries, due to a more prominent neutron flux peak. The fast neutron component, calculated using the JENDL-5.0 neutron library, was 23.42%-63.94% lower compared to other libraries, while the gamma-ray component derived from the JEFF-3.3, CENDL-3.2, and JENDL-5.0 neutron libraries was 6.79%-10.08% higher than that from the ENDF/B series. Further analysis revealed that the discrepancies were primarily caused by differences in the neutron cross-section data of F, Pb, Mg, Cu, and H in specific neutron libraries. In particular, the differences in the neutron cross-sections of F and Pb accounted for the variations in the obtained BSA outlet spectra and neutron parameters when using the ENDF/B VIII.1 and JENDL-5.0 neutron libraries. The elevated gamma-ray component observed in the JEFF-3.3 and CENDL-3.2 neutron libraries, compared to the ENDF/B series, was largely due to the different cross-sections of Mg, Cu, and H. These findings underscored the considerable discrepancies arising from variations in nuclear data libraries and emphasized the critical importance of appropriate selection of nuclear data libraries for BNCT applications.